Ameliorative Effects of Aloe Vera Gel Extract on Circulatory and Tissue Lipid Profile Status in Streptozotocin-Induced Diabetic Rats (Bangladesh Journal of Medical Biochemistry, 2018)
Diabetes is characterized by hyperglycaemia with alterations of lipid parameters. The effects of Aloe vera (A.V) gel extract on lipid profiles of streptozotocin-induced diabetic rats were investigated. Seventy-two male albino rats were randomly divided into six groups of 12 rats each; control, diabetic control, 4 ml/kg and 8 ml/kg body weight (b.w.) A.V, 10 mg/kg b.w. glibenclimide and non-diabetic 8 ml/kg b.w. A.V groups. They were treated for 14 and 28 days. The plasma and HDL lipid profiles (triacylglycerols, cholesterol and phospholipids) of the diabetic rats were significantly (p